Therapeutic Potential of Palmitoylethanolamide in Gastrointestinal Disorders - Marija Branković; Tijana Gmizić; Marija Dukić; Marija Zdravković; Branislava Daskalović; Davor Mrda; Novica Nikolić; Milica Brajković; Milan Gojgić; Jovana Lalatović; Đorđe Kralj; Ivana Pantić; et al. (MDPI AG, 2024)
Palmitoylethanolamide (PEA) is an endocannabinoid-like bioactive lipid mediator belonging to the family of N-acylethanolamines, most abundantly found in peanuts and egg yolk. When the gastrointestinal (GI) effects of PEA are discussed, it must be pointed out that it affects intestinal motility but also modulates gut microbiota. This is due to anti-inflammatory, antioxidant, analgesic, antimicrobial, and immunomodulatory features. Additionally, PEA has shown beneficial effects in several GI diseases, particularly irritable bowel syndrome and inflammatory bowel diseases, as various studies have shown, and it is important to emphasize its relative lack of toxicity, even at high dosages. Unfortunately, there is not enough endogenous PEA to treat disturbed gut homeostasis, even though it is produced in the GI tract in response to inflammatory stimuli, so exogenous intake is mandatory to achieve homeostasis. Intake of PEA could be through animal and/or vegetable food, but bearing in mind that a high dosage is needed to achieve a therapeutic effect, it must be compensated through dietary supplements. There are still open questions pending to be answered, so further studies investigating PEA's effects and mechanisms of action, especially in humans, are crucial to implementing PEA in everyday clinical practice.